2021
DOI: 10.1063/5.0040035
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of plasma activated water by gliding arc at atmospheric pressure: Effect of the chemical composition of water on the activation

Abstract: Plasma activated water is a chemically active aqueous medium characterized by the presence of reactive oxygen and nitrogen species created by plasma exposure. This particular chemical composition is the starting point of extensive research studies in several domains such as bio-disinfectant in biomedical applications or as fertilizer in agricultural applications. These various applications need adjustments of the PAW properties and consequently require a better control of the PAW chemical composition. To achie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 28 publications
0
13
0
Order By: Relevance
“…Many studies have reported that PAW production using different types of water, including deionized water, distilled water, tap water, and reverse osmosis water affects the PAW antimicrobial effectiveness. Wartel et al (2021) noted that the post-discharge reactions on the concentration profile behavior of nitrite and nitrate during the PAW generation via a gliding arc discharge with distilled water were different to tap water. Figure 8a shows degradation of nitrite with an increase in the mole concentration of nitrate during the storage time.…”
Section: Type Of Water and Water Conductivitymentioning
confidence: 99%
“…Many studies have reported that PAW production using different types of water, including deionized water, distilled water, tap water, and reverse osmosis water affects the PAW antimicrobial effectiveness. Wartel et al (2021) noted that the post-discharge reactions on the concentration profile behavior of nitrite and nitrate during the PAW generation via a gliding arc discharge with distilled water were different to tap water. Figure 8a shows degradation of nitrite with an increase in the mole concentration of nitrate during the storage time.…”
Section: Type Of Water and Water Conductivitymentioning
confidence: 99%
“…In contrast, indirect application is when plasma activates a liquid that will be used for a specific application [ 2 , 14 ]. The most used discharges for PJ generation are dielectric barrier discharge (DBD) and gliding arc (GA) [ 11 , 12 , 15 , 16 , 17 , 18 , 19 , 20 , 21 ]. However, the nature of each unloading application may vary slightly within the same area of knowledge; for example, the DBD plasma jet is best suited for wound and tumor treatments [ 22 , 23 , 24 , 25 ] due to lower operating temperature, and does not generate an arc, which can cause a burn on living tissues [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, the nature of each unloading application may vary slightly within the same area of knowledge; for example, the DBD plasma jet is best suited for wound and tumor treatments [ 22 , 23 , 24 , 25 ] due to lower operating temperature, and does not generate an arc, which can cause a burn on living tissues [ 7 ]. In contrast, for the activation of large volumes of liquids and in the inactivation of fungi, the PJs that generate higher concentrations of RONS are the GA [ 12 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…These measurement methods can be also found in some relevant references. [20,21] The content of ozone (O 3 ) in the solution was measured by iodometry. The O 3 can react with iodide ions leading to the formation of iodine.…”
mentioning
confidence: 99%
“…Due to these advantages, gliding arc discharge plasma has been widely concerned, but the gliding arc discharge plasma in the existing research is all realized in the gas phase. Although there are some applications in water treatment, [19,20] it is necessary to blow the arc plasma initiated in the gas phase into the liquid, which leads to the low gas-liquid mass transfer efficiency. Therefore, how to directly initiate gliding arc plasma in liquid is a very meaningful topic.…”
mentioning
confidence: 99%